Obstacles to the Quality of Education According to the Credit Hour System at the College of Physical Education and Sports Sciences University of Samarra - Mohammed, Azzam Makki; Abdulmaged, Mustafa Ahmed; Al-Samarrai, Ammar Fares Attia (Universitas Pejuang Republik Indonesia, 2025)
Research Objectives: To construct a questionnaire on the obstacles to the quality of education according to the credit hour system from the faculty members' perspective. To identify the obstacles to the quality of education according to the credit hour system. The researchers used the descriptive methodology with a survey method due to its suitability for the nature of the research. The research population and sample were selected from the faculty members of the College of Physical Education and Sports Sciences / University of Samarra, numbering (33). The researchers employed several statistical tools to reach results that achieve the research objectives. The researchers concluded that obstacles to the quality of education according to the credit hour system exist. The item